Penerapan Teknologi Ekstraksi Oleoresin Jahe (Zingiber Officinale) Ramah Lingkungan dan Konvensional - Nanda Aurelia Salsabila S (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Ginger waste, including peel and residue from herbal extract or beverage industries, still contains valuable bioactive compounds such as gingerol, shogaol, and zingerone. These compounds have significant potential as multifunctional bioactive ingredients in food, pharmaceutical, and cosmetic applications. This review aims to summarize and compare various extraction methods for ginger oleoresin from waste materials, including conventional techniques (maceration and Soxhlet) and advanced green extraction methods such as Ultrasound-Assisted Extraction (UAE), Microwave-Assisted Extraction (MAE), and Supercritical CO₂ Extraction (SC-CO₂). The findings indicate that modern extraction techniques offer higher yield, shorter processing time, and greater selectivity of active compounds compared to traditional methods. Process modifications, including enzymatic pretreatment and three-phase partitioning, have been shown to enhance oleoresin recovery and quality. Key challenges include the development of green solvents, optimization of process parameters, and preservation of bioactive stability. Further research is needed to establish efficient and sustainable extraction approaches suitable for natural product research.